TEXNOLOGIK TA’LIM JARAYONIDA KOMPETENSIYAVIY YONDASHUVNING PEDAGOGIK ASOSLARI. (Universal International Scientific Journal, 2026)
This article discusses the issues of further improving the education system in our republic. In particular, the formation of competencies in learners, the use of a competency-based approach in the educational process, and the importance of this approach in improving the quality of education, especially in technological education, are analyzed.
Keywords: PEDAGOGICAL FOUNDATIONS OF THE COMPETENCY-BASED APPROACH IN THE PROCESS OF TECHNOLOGICAL EDUCATION.